PELATIHAN KEWIRAUSAHAAN STRATEGI PENGEMBANGAN BISNIS DAN IMPLEMENTASI EXCELLENT SERVICE PADA KELOMPOK LASKAR SHOLAWAT KECAMATAN PATRANG JEMBER - Ahmad Sauqi (STIE Mandala Jember, 2021)
Community service with the theme of business development strategy and implementation of excellent service is carried out at the Laskar Sholawat Commissariat which is located at Jl. Watermelon II No. 2 Patrang District, Jember Regency. There are 16 participants in this entrepreneurship training. Most of the training participants are already entrepreneurs by running small businesses, including in the fields of electronic services, embroidery, cakes, handicrafts, snack traders, livestock, plantations and online shops. Referring to the partner's problems, the servant will provide training on strategies to create customer satisfaction with the concept of excellent service. building a business strategy from 4 basic management foundations, including financial management (don't mix business financial management and family financial management), operational management (how to build service quality or product quality), HR management (how to build a strong personality in entrepreneurship) and marketing management (how to respond to existing opportunities and always update with all market developments) and Marketing strategy training with marketing implementation through E-Commerce. Keywords: Strategy; Business; Implementation; Excellent; Services.